(untitled) (Research, Society and Development, 2020)
The Lean Philosophy is a business strategy used to increase customer satisfaction through better use of company resources. The success in its application has a strong cultural dependence due to the involvement of people and the continuous improvement of the organization’s internal processes. In this context, this article aimed to analyze the relationship between Lean Philosophy and Organizational Culture through a bibliographic study that allows the evaluation of the application of Lean Philosophy in Organizational Culture. The searches were carried out on the digital bases of Web of Science and Scopus within a period of 10 years, and the bibliometric behavior between the two themes was analyzed. A qualitative and statistical research was used to measure production indexes, as well as to monitor the development of Organizational Culture and Lean Philosophy and their relationships through the evolution of publications. The results found show a relationship between the two areas, as verified in the results of this research, Organizational Culture is an older theme and guides the way organizations behave, however, after the emergence of Lean Philosophy, it can be perceived that the authors of these two subjects are mentioned and related, demonstrating that Lean Philosophy can be associated with Organizational Culture in a way that starts to shape it for the benefit of the client.